Anatomical and Functional Results of Early or Late Switching from Anti-VEGF to Dexamethasone Implant in Case of Poor Anatomical Response in Naïve Patients with Macular Edema Secondary to Branch Retinal Vein Occlusion - Yozgat, Zübeyir; Işik, Mehmed Uğur (Informa UK Limited, 2024)
To compare the outcomes of early or late switching from intravitreal (IV) anti-vascular endothelial growth factor (anti-VEGF) injection to IV Dexamethasone (DEX) implant injection in treatment-naïve patients with macular edema secondary to branch retinal vein occlusion.This study included 68 eyes of 68 treatment-naïve BRVO patients who started anti-VEGF treatment. After the loading dose, the patients were divided into two groups: Early DEX group (n:34) (DEX implant treatment started after 3 loading doses) and Late DEX group (n:34) (DEX implant treatment started after 6 months). Visual acuity and examination findings were recorded at baseline, 3rd, 6th, and 12th month follow-ups. Optical coherence tomography data were recorded for central macular subfield thickness assessment.A total of 30 (44.1%) women and 38 (55.9%) men participated, and the average age was 67.6 ± 6.4 years. The mean letter gains at week 52 was 15.1 and 20.9 in the Early DEX and Late DEX groups, respectively. The group with the highest gain of ≥15 letters was the Late DEX group (26/34 patients) and the gain of ≥15 letters was 14/34 in the Early DEX group (p: 0.006). At week 52, the anatomical gain was 115.3 µm and 136.9 µm in the Early DEX and Late DEX groups, respectively.A gain of 15 or more letters was demonstrated to be higher in patients who switched to DEX implant late after anti-VEGF treatment. If it is necessary to switch, the late switch may be more effective for more visual gain at the end of the first year.
Keywords: Male; Drug Implants; Treatment Outcome; Retinal Vein Occlusion; Intravitreal Injections; Humans; Female; Middle Aged; Glucocorticoids; Dexamethasone; Macular Edema; Aged; Retrospective Studies